Serum biochemical panel and modulation of skeletal muscle fibres: effect on the meat quality from lambs fed with different levels of whole cottonseed - Monego , Magda Aita (2022)
The use of whole cottonseed (WCS) in the diet of ruminants has come to prominence mainly because this ingredient contains high levels of protein and lipids. The aims of this study were to evaluate serum biochemical panel and modulation of the skeletal muscle fibres (Longissimus thoracis) of Ile de France lambs fed with levels of WCS; and relationship between skeletal muscle fibres and meat quality. Fifty lambs were used in the experiment: five (5) reference and 45 equally distributed in treatments 0, 10, 20, 30 and 40% WCS (64 days feedlot time), using a completely randomised design. Blood biochemical determinations were performed using colorimetric kits. The fibers were determined by histochemistry method and classified as Type I, Type IIA, Type IIB and Type IIC. Muscle fiber characteristics were correlated with meat quality, considering variables of color, texture and sensory profile, physicochemical and fatty acid profile. Cholesterol levels, total protein and gamma-glutamyl transferase increased (p≤0.05) in line with increased levels of WCS in the diet. Muscle fibres modulation (p≤0.05) was observed, with an increase in red, a reduction in glycolytic, and modulation of Type IIB to Type IIA. The addition of WCS to the diet increased (p≤0.05) the relative area of Type IIC. There was correlation between muscle fibres and meat qualitative characteristics. Time effect was more pronounced than diet effect on the muscle fibres modulation. Muscle fibres modulation was closely linked with meat quality.